Special Education Teachers’ Skills and Knowledge in Handling Students with Hearing Problems in Special Education Integration Program.: Pengetahuan dan Kemahiran Guru Pendidikan Khas dalam Melaksanakan Program Pendidikan Khas Integrasi (PPKI) Masalah Pendengaran - Selvam, Dashwini; Anal, Ardzulyna binti (Jurnal Pendidikan Bitara UPSI, 2022)
This study aims to explore the challenges faced by special education teachers in the PPKI Hearing Problems from the aspect of knowledge and readiness of special education teachers with hearing problems. A qualitative study in the form of a case study was conducted by purposive sampling consisting of heteregeneous sampling involving six special education  teachers with hearing problems from the Special Education Integration Program in one of the primary schools. Two types of research instruments were used in this study namely interviews, observation without participants. The data of this study were thematically  analyzed by using Nvivo version 12. The results of this study show that special education teachers for hearing impairment in this study location face challenges such as lack of exposure to the world of special education for hearing impairment because most of the study samples do not have a special education degree for hearing impairment and lack skills in Signed Hand Code Language (KTBM) . The findings of this study also identify that teachers are also faced with very low classroom management skills and the guidelines provided also do not include inputs that can help special education teachers of hearing problems.